MHC Genotyping by SSCP and Amplicon-Based NGS Approach in Chamois - Sunčica Stipoljev; Elena Bužan; Barbora Rolečková; Laura Iacolina; Nikica Šprem (Animals, 2020)
Genes of the major histocompatibility complex (MHC) code for cell surface proteins essential for adaptive immunity. They show the most outstanding genetic diversity in vertebrates, which has been connected with various fitness traits and thus with the long-term persistence of populations. In this study, polymorphism of the MHC class II DRB locus was investigated in chamois with Single-Strand Conformation Polymorphism (SSCP)/Sanger genotyping and Ion Torrent S5 next-generation sequencing (NGS). From eight identified DRB variants in 28 individuals, five had already been described, and three were new, undescribed alleles. With conventional SSCP/Sanger sequencing, we were able to detect seven alleles, all of which were also detected with NGS. We found inconsistencies in the individual genotypes between the two methods, which were mainly caused by allelic dropout in the SSCP/Sanger method. Six out of 28 individuals were falsely classified as homozygous with SSCP/Sanger analysis. Overall, 25% of the individuals were identified as genotyping discrepancies between the two methods. Our results show that NGS technologies are better performing in sequencing highly variable regions such as the MHC, and they also have a higher detection capacity, thus allowing a more accurate description of the genetic composition, which is crucial for evolutionary and population genetic studies.